2022
DOI: 10.3390/ijerph192215227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Anti-HIV-1 Protein from Momordica balsamina Leaf Extract

Abstract: Our lab investigates the anti-HIV-1 activity in Momordica balsamina (M. balsamina) leaf extract. Traditional Senegalese healers have used M. balsamina leaf extract as a part of a plant-based treatment for HIV/AIDS infections. Our overall goal is to define and validate the scientific basis for using M. balsamina leaf extract as a part of the traditional Senegalese treatment. As an initial characterization of this extract, we used activity-guided fractionation to determine the active ingredient’s solubility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This finding is in line with the work of Coleman et al (2022) [49]. They found that the aqueous extract of M. balsamina leaves inhibits HeLa-CD4+-LTR-βgal cells with HIV-1 NL4-3 by more than 50% at concentrations of 0.02 mg/mL and above, with no toxicity in the 0-0.5 mg/mL range [49]. Other antiviral properties of the plant have been demonstrated.…”
Section: Biological Properties Of Momordica Balsaminasupporting
confidence: 85%
See 1 more Smart Citation
“…This finding is in line with the work of Coleman et al (2022) [49]. They found that the aqueous extract of M. balsamina leaves inhibits HeLa-CD4+-LTR-βgal cells with HIV-1 NL4-3 by more than 50% at concentrations of 0.02 mg/mL and above, with no toxicity in the 0-0.5 mg/mL range [49]. Other antiviral properties of the plant have been demonstrated.…”
Section: Biological Properties Of Momordica Balsaminasupporting
confidence: 85%
“…In fact, the plant protein MoMo30 (30 kDa protein), isolated from M. balsamina, effectively inhibits HIV-1 in vitro at nanomolar levels while exhibiting minimal cellular toxicity at inhibitory concentrations [48]. This finding is in line with the work of Coleman et al (2022) [49]. They found that the aqueous extract of M. balsamina leaves inhibits HeLa-CD4+-LTR-βgal cells with HIV-1 NL4-3 by more than 50% at concentrations of 0.02 mg/mL and above, with no toxicity in the 0-0.5 mg/mL range [49].…”
Section: Biological Properties Of Momordica Balsaminasupporting
confidence: 74%
“…We have previously shown that extracts of Momordica balsamina made in water contain antiviral activity [ 33 ]. The active agent is a 30 kDa protein we call MoMo30.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of water extracts from plants has been previously described [ 33 ]. One hundred grams of dried and milled leaves from Momordica balsamina were extracted in 1L of distilled water overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation